2020
DOI: 10.1007/s11666-020-01087-6
|View full text |Cite
|
Sign up to set email alerts
|

Study on Deposition Behavior of Less Than 5 μm YSZ Particles in VLPPS

Abstract: A particular YSZ feedstock for very low-pressure plasma spraying (VLPPS) has been designed which can be automatically divided into less than 5 μm YSZ molten particles in the long plasma jet. Fully molten particles were deposited on the substrate at different deposition distances of 250, 350 and 450 mm, respectively. The deposition behavior of less than 5 μm YSZ molten particles were studied aiming to obtain a thin gastight YSZ coating. The flattening ratio of particles at different deposition distances and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Wang et al [6] observed that the flattening level of droplets increases with increased substrate temperature. Similarly, Gao et al [10] found that the flattening level increases as the spray pressure decreases. Notably, existing methods cannot readily attend to the flattening behavior of an individual droplet, primarily due to the many restricting factors during actual plasma spraying processes.…”
Section: Introductionmentioning
confidence: 80%
“…Wang et al [6] observed that the flattening level of droplets increases with increased substrate temperature. Similarly, Gao et al [10] found that the flattening level increases as the spray pressure decreases. Notably, existing methods cannot readily attend to the flattening behavior of an individual droplet, primarily due to the many restricting factors during actual plasma spraying processes.…”
Section: Introductionmentioning
confidence: 80%
“…To ensure good adhesion and minimize splashing of the incoming molten droplets on the underlying material [19,[35][36][37][38] and improved ionic conductivity [12], it is important that the substrate temperature is >600 • C, the critical bonding temperature for YSZ [15,16]. The thermal history of the 4 spray runs as measured by a thermocouple onboard the high-speed rotating substrate holder is illustrated in Figure 2.…”
Section: Ysz Deposition Temperaturementioning
confidence: 99%
“…Here, we expand upon prior work of APS YSZ deposition at high TSRVs (≥3.8 m/s) [5,6] by fabricating electrolytes at >800 • C, with the goal of reducing segmentation cracking and leak rates without the use of post-fabrication densification steps [17,18] or zirconium nitrate impregnations [11]. While it is well established that highly dense, low leak rate electrolytes can be fabricated using lowpressure environments [2,9,19], we continue to utilize APS due to its comparatively lower costs and reduced processing times [20,21]. APS NiO-YSZ coatings were prepared on substrates utilizing a recently developed CuO surface treatment in order to reduce fuel electrode roughness for subsequent YSZ deposition.…”
Section: Introductionmentioning
confidence: 99%